Adaptation to reductions in chilling availability using variation in PLANT HOMOLOGOUS TO PARAFIBROMIN in Brassica napus - Warner, Samuel; O’Neill, Carmel M.; Doherty, Rebecca; Wells, Rachel; Penfield, Steven (Frontiers in Plant Science, 2024)
Winter annual crops are sown in late summer or autumn and require chilling to promote flowering the following spring. Floral initiation begins in autumn and winter and in winter oilseed rape (OSR) continued chilling during flower development is necessary for high yield potential. This can be a problem in areas where chilling is not guaranteed, or as a result of changing climates. Here we used chilling disruption and low chilling to identify loci with the potential to increase chilling efficiency in winter OSR. We report that time to flowering and yield potential under low chill conditions is affected by variation at the PLANT HOMOLOGOUS TO PARAFIBROMIN gene, a component of the plant PAF1c complex. We show that increases in winter chilling given to developing flowers can improve seed yields and that loss of function of BnaPHP.A05 leads to early flowering in B. rapa and B. napus and an increase in seed set where chilling is limited. Because PHP is known to specifically target the FLOWERING LOCUS C (FLC) gene in Arabidopsis we propose that variation at PHP is useful for breeding modifications to chilling responses in polyploid crops with multiple copies of the FLC gene.